Pengaruh Penggunaan Teknologi, Dukungan Keluarga, Dan Gaya Belajar Terhadap Keterampilan Literasi Digital Mahasiswa UNNES - Althaf Nabighah, Naufhal; Raharjo, Teguh Hardi (Universitas Hamzanwadi, 2026)
This study aims to examine the influence of technology use, family support, and visual learning styles on the digital literacy skills of students at Universitas Negeri Semarang. The type of research employed in this study is quantitative with a descriptive approach. The research design used is a survey design. The population in this study comprises all students of Universitas Negeri Semarang. The sampling technique used is probability sampling. The subjects of this study are students of Universitas Negeri Semarang. Data were collected through the distribution of questionnaires using a Likert scale. This research utilizes causal quantitative data, which are measurable and expressed in numerical form.. The results of the coefficient of determination test show an R² value of 0.627, indicating that technology use, family support, and learning style collectively influence students’ digital literacy skills by 62.7%. Theremaining 37.3% is explained by other factors not included in this research model. Based on the t-test, the first hypothesis has a probability value of 0.001 < 0.05, indicating that technology use has a positive and significant effect on students’ digital literacy skills. The second hypothesis has a probability value of 0.044 < 0.05, suggesting that family support also has a positive and significant effect on digital literacy skills. The third hypothesis shows a probability value of 0.001 > 0.05, which confirms that visual learning style has a positive and significant effect on digital literacy skills. The fourth hypothesis has a probability value of <0.001, which is far below 0.05, indicating that all independent variables collectively have a significant effect on the dependent variable. Future researchers are encouraged to expand the research model by incorporating mediating or moderating variables to develop a more complex framework and produce more comprehensive findings.